2017
DOI: 10.1021/acs.biomac.7b00393
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Salt Induced Microphase Separation To Form Soy Protein Microcapsules or Microgels in Aqueous Solution

Abstract: Self-assembly of native glycinin at room temperature was investigated as a function of the pH and the NaCl concentration. Microphase separation leading to the formation of dense protein microdomains was observed by confocal laser scanning microscopy. Depending on the conditions, the microdomains coalesced into a continuous protein rich phase or associated into large clusters. Addition of β-conglycinin inhibited phase separation and reduced the pH range in which it occurred. Microdomains of glycinin that were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 47 publications
5
47
0
Order By: Relevance
“…The solubility of glycinin is further decreased by lowering the temperature ( Lakemond, de Jongh, Hessing, Gruppen, & Voragen, 2000;Wolf & Sly, 1967). In a recent study, Chen et al (2017b) show that the low solubility of glycinin at 0.1-0.2 M is related to the coacervation of glycinin. Initially, spherical protein rich domains are formed that with time coalesce into a continuous layer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The solubility of glycinin is further decreased by lowering the temperature ( Lakemond, de Jongh, Hessing, Gruppen, & Voragen, 2000;Wolf & Sly, 1967). In a recent study, Chen et al (2017b) show that the low solubility of glycinin at 0.1-0.2 M is related to the coacervation of glycinin. Initially, spherical protein rich domains are formed that with time coalesce into a continuous layer.…”
Section: Introductionmentioning
confidence: 99%
“…Simple coacervation has been observed for plant proteins, including soy glycinin (Chen, Zhao, Nicolai, & Chassenieux, 2017b), pea protein (Cochereau, Nicolai, Chassenieux, & Silva, 2019), broadbean protein (Popello, Suchkov, Grinberg, & Tolstoguzov, 1992), gliadin (Boire, Menut, Morel, & Sanchez, 2013), zein (Muthuselvi & Dhathathreyan, 2006) and kafirin (Oguntoyinbo, Taylor, & Taylor, 2018). However, compared to the complex coacervation that usually occurs between oppositely charged proteins and polysaccharides (Schmitt & Turgeon, 2011), the investigation of the simple coacervation of protein is still quite limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Producing adequate quantities of protein microgels via these methods may appear problematic, but with more research into practical processing methods this is likely be solved. Indeed, Chen et al (Chen et al, 2017b) have even shown that soy protein microgels can form 'spontaneously' from raw materials on simple changes in solution conditions. Thermally induced cross-linking can be supplemented by further chemical (Kang and Kim, 2010) or enzymatic (Guo et al, 2016) cross-linking, but this runs the risk of decreasing the acceptability of such materials in foods.…”
Section: Methods Of Preparation Of Microgelsmentioning
confidence: 99%
“…In aqueous environment, both these components show peculiar behavior of globular molecules consisting of a hydrophilic shell and a hydrophobic kernel, together with a certain amount of small water‐soluble aggregates. A range of colloidal structures (microparticles, hydrogels, composite blends, fibrils, and nanoparticles) can be obtained by inducing and controlling aggregation of soy protein isolate (SPI) molecules in aqueous media by manipulating external factors such as temperature and pH or by addition of salt, desolvent, or crosslinking agents. The ligand‐binding properties of SPI make it an excellent carrier material for developing delivery systems for various hydrophobic and hydrophilic bioactive compounds.…”
Section: Starting Materials For Fabricating Functional and Engineeredmentioning
confidence: 99%